Feasibility and Safety of an Operative Tool for Anterior Chronic Exertional Compartment Syndrome Treatment. (December 2015) - de Bruijn, Johan A.; van Zantvoort, Aniek P. M.; Winkes, Michiel B.; Raaymakers, Leo; van der Cruijsen-Raaijmakers, Marike; Hoogeveen, Adwin R.; Scheltinga, Marc R.
Background: Operative management of chronic exertional compartment syndrome of the tibialis anterior muscle compartment (ant-CECS) usually involves the use of a fasciotome. Collateral tissue damage such as hematoma and nerve damage may occur during the procedure. The current report assessed the feasibility and safety of an alternative tool for the operative management of ant-CECS. Methods: The system had a speculum-like hollow tube that was inserted via a 2-cm skin incision and allowed for the protected advancement of a fasciotome. The device was tested in patients with bilateral ant-CECS. Symptoms were prospectively scored before and after surgery using a 5-category verbal rating scale (VRS). Fourteen patients (age 26 ± 10 years) were analyzed. Complications and operative efficacy were determined using physical examination and questionnaires after 21 (range = 16-25) months. Results: Technical operative success rate was 100% (28/28 legs). Operation time was 10 ± 2 minutes per leg (range = 6-14). Perioperative complications were not observed. One superficial wound infection was treated nonoperatively. Significant reductions in pain (–2.2 ± 1.1 on 5-point VRS, P < .001), tightness (–1.9 ± 1.6, P = .01), cramps (–1.4 ± 1.6, P = .009), muscle weakness (–1.6 ± 1.2, P < .001), and altered sensibility (–1.3 ± 1.4, P = .005) were registered 21 months postoperatively. Conclusion: This fasciotome was simple to use and allowed for a safe fasciotomy in patients with leg ant-CECS. A randomized controlled trial comparing the present device with a widely used fasciotome was under way at the time of writing of this study. Level of evidence: Level IV, case series